2022
DOI: 10.7150/thno.69446
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinate improves metabolic recovery and cell survival of the liver following cold preservation

Abstract: Rationale: Hibernating thirteen-lined ground squirrels (GS; Ictidomys tridecemlineatus ) are naturally adapted to prolonged periods of ultraprofound hypothermia (body temperature < 5 ºC) during torpor, and drastic oscillations of body temperature and ischemia/reperfusion-like stress during their short euthermic interbout arousals. Thus, their superior adaptability may hold tremendous promise for the advancement of donor organ cold preservation and subsequent organ transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…Liver tissue were weighted and homogenized in lysis buffer 7 . Then 100 μL sample and PBG standard were mixed with 100 μL fresh Modified Ehrlich reagent and incubated for 10 minutes at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver tissue were weighted and homogenized in lysis buffer 7 . Then 100 μL sample and PBG standard were mixed with 100 μL fresh Modified Ehrlich reagent and incubated for 10 minutes at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we revealed that the non-proteinogenic amino acid 5-Aminolevulinate (5-ALA) is associated with stress responses to cold storage-rewarming and hypoxia-reoxygenation in the hepatocyte-like cells derived from the induced pluripotent stem cells of a hibernating mammal 7 . Addition of 5-ALA into the cold storage solution for human stem cell-derived hepatocyte-like cells could substantially alleviate rewarming-induced mitochondrial ROS overproduction and dysfunction in energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that cold resistance is not observed in non-hibernators, including strict homeotherms, such as humans, and heterotherms, such as mice, not only at whole body level but also at tissues and cellular levels ( Lyman et al, 1982 ); When exposed to extreme cold temperatures lower than 10°C, primary cultured cells or tumor cells from non-hibernators such as humans, mice, and rats die within a day or several days, but those from hibernators can survive for over 5 days ( Hendriks et al, 2017 ; Ou et al, 2018 ; Hendriks et al, 2020 ; Anegawa et al, 2021 ). Such difference in cold resistance between hibernators and non-hibernators is also observed in neurons and hepatocytes differentiated from induced pluripotent stem cells (iPSC) derived from a hibernator thirteen-lined ground squirrels (13LGS) ( Ictidomys tridecemlineatus ), highlighting the cell-intrinsic properties of cold resistance and cellular homeostasis in hibernators ( Ou et al, 2018 ; Zhang et al, 2022 ). Interestingly, such cell-intrinsic properties to sustain cellular homeostasis under cold conditions may also be observed in embryonic stem (ES) cells of mice ( Mus musculus ), which do not hibernate but do fasting-induced torpor (FIT), and are therefore classified as heterotherms.…”
Section: Cell-intrinsic Cold Resistancementioning
confidence: 97%
“…One promising and powerful solution for clarifying the mechanisms of cold resistance is to directly manipulate genes. Comparative metabolomic analysis of hepatocyte-like cells derived from 13LGS-iPSCs revealed that 5-aminolevulinate (5-ALA), a metabolite produced in the first step of the heme synthesis pathway from glycine and succinyl-CoA, increased after 4 h of cold treatment, and is seemingly required for cold resistance of these cells because knockdown of 5-aminolevulinate synthase 1 (ALAS1) led to overproduction of ROS from mitochondria during cooling and rewarming ( Zhang et al, 2022 ). Moreover, the authors demonstrated that liver organs harvested from rats treated at 4°C for 48 h with 5-ALA decreased cell stress and cell death markers in the process of rewarming compared to those without it.…”
Section: Genetic Basis Of Defenses Against Cold In Hibernatorsmentioning
confidence: 99%
“…Since mammalian specimens can slow down or even suspend their in vitro metabolic activity and decay time at low temperatures, they are usually stored in non-physiological low-temperature conditions to prolong their preservation period [ 5 ]. They can be preserved in two states: either at deep cryogenic temperatures in frozen/vitrified states with totally suspended animation for months or even years (cryopreservation usually refers to temperatures from −80 to −196 °C) or at hypothermic temperatures without phase transition with partially decreased animation for hours or days (hypothermic storage around 4 °C) [ 6 , 7 ]. Due to its indispensable role in the supply chain of biological specimens, biopreservation is ubiquitously used in biomedical and clinical research and applications, such as assisted reproduction [ 8 , 9 , 10 ], stem cell therapy [ 11 , 12 ], regenerative medicine [ 13 ], tissue engineering [ 14 ], and mRNA medicine [ 15 ].…”
Section: Introductionmentioning
confidence: 99%